The Impact of Digital Transformation on Entrepreneurial Innovation in Emerging Economies - Putri Ayu Astuti; Desi Romandani; Afifah Arum (International Forum of Researchers and Lecturers, 2024)
This paper explores the relationship between digital transformation and entrepreneurial innovation within emerging economies. As the world becomes increasingly digitized, entrepreneurs are leveraging new technologies to innovate and create disruptive solutions. The study examines how digital tools, such as artificial intelligence, blockchain, and cloud computing, are being utilized by entrepreneurs to enhance productivity, streamline operations, and develop new business models. The research highlights key success factors, challenges, and opportunities faced by entrepreneurs in emerging markets and provides recommendations for integrating digital transformation into entrepreneurial strategies.